Predictors of EGF receptor monoclonal antibody activity in metastatic colorectal cancer: current status. (October 2012) - Modest, Dominik Paul; Giessen, Clemens; Stintzing, Sebastian
SUMMARY In the treatment of metastatic colorectal cancer, the cytostatic drugs 5-fluorouracil, irinotecan and oxaliplatin, as well as the VEGF antibody bevacizumab, are applied without the use of predictive biomarkers. To date, KRAS mutational status is the only accepted predictive biomarker, limiting the use of the EGF receptor (EGFR) monoclonal antibodies cetuximab and panitumumab to patients with KRAS wild-type tumors. The different KRAS mutations on codons 12 and 13 represent a negative predictive biomarker with poor positive predictive power. The negative predictive value of KRAS mutations has been questioned by several retrospective analyses of clinical trials, hypothesizing variable efficacies of EGFR antibodies associated with the diverse range of mutations. While the BRAF mutation is associated with a negative prognosis, its predictive value in the context of EGFR monoclonal antibody therapy is not fully understood. The present review aims to outline possible clinical and molecular biomarkers of EGFR monoclonal antibodies in metastatic colorectal cancer.